Kinematics Analysis of Humanoid Robot based on Motion Capture Technology and Gait Simulation - Wenyuan Wang; Rongchang Fu; Fu Cao (Jixie chuandong)
Based on the human structure as the prototype， a humanoid robot with a lower limb and 7 degrees of freedom is designed based on bionics. The motion coordinates of human body during normal walking are collected through the three-dimensional optical motion capture system， and the joint angle and the variation rule of the moment of each lower extremity joint during walking are obtained by analyzing the data. A 7-degree-of-freedom kinematics model of the lower extremity is established and inverse kinematics analysis is carried out to solve the variation of the lower extremity joint angles. According to the gait programming， the rotation angles of the lower extremity joints during the humanoid robot walking are solved. In the lower extremity in UG environment， the 3D model of 7 DOF humanoid robot is established， and the dynamics simulation is carried out by using multi-body dynamics software Adams， combining with the gait motion planning from the angle of the changing situation to set the simulation parameters， through virtual prototype humanoid robot gait， and the simulation data and the data results from the motion capture experimental are compared. Research results show， the humanoid robot can achieve stable walking gait， the overall accuracy of the modeling ideas， analysis of kinematics and dynamics simulation is confirmed. Based on the results of the experiment simulation for hip and knee torque value compared with the experimental value of relative error of 6.7% and 9.6% respectively in a reasonable scope， the basis for the humanoid robot structure design and motor selection is provided.